A clinical evaluation of a sensor to detect blockage due to crystalline biofilm formation on indwelling urinary catheters. (14th March 2014) - Long, Adele; Edwards, Julia; Thompson, Richard; Lewis, Debbie A.; Timoney, Anthony G.
<x xml:space="preserve">Abstract</x> Objective To test the performance and acceptability of an early warning sensor to predict encrustation and blockage of long‐term indwelling urinary catheters. Patients and Methods In all, 17 long‐term indwelling catheter users, 15 'blockers' and two 'non‐blockers' (controls) were recruited; 11 participants were followed prospectively until catheter change, three withdrew early and three did not start. Two sensors were placed in series between the catheter and the urine bag at catheter change. The sensor nearest the bag was changed at the same time as the bag change (weekly); the sensor nearest the catheter remained in situ for the duration of the catheter's life. Bacteriology and pH determinations were performed on urine samples at each bag, sensor and catheter change. The colour of the sensors was recorded daily. On removal, each sensor and the catheter were examined for visible evidence of encrustation and blockage. Participants were asked to keep a daily diary to record colour change and any other relevant observations and to complete a psychosocial impact of assistive devices tool at the end of the study. Participants and carers/healthcare professionals (when involved in urine bag or catheter change) were asked to complete a questionnaire about the sensor. Results Urease‐producing bacteria were isolated from seven of the 14 patients (including early withdrawals; P. mirabilis in four, Morganella or Providencia in three). In six of the seven patients the sensors turned blue‐black; two of these were early withdrawals, two went to planned catheter change (one of these was recruited as a 'non‐blocker') and three had catheter blockage. The number of days of catheterisation before blockage was 22, 23 and 25 days, and the sensor changed colour within 24–48 h after insertion. The urine mean (range) pH of the sensors that turned blue‐black was 7.6 (5.5–9.0) and of the sensors that remained yellow 6.1 (5.1–7.5). The sensor was generally well‐received and was positive in the psychosocial assessment. Conclusions The sensor is a useful indicator of urine pH and of the conditions that lead to catheter blockage. It may be particularly useful for new indwelling catheter users. To be a universally acceptable predictor of catheter blockage, the time from sensor colour change to blockage needs to be reduced.